Study on heat transfer characteristic parameters and cooling effect of cold wall cooling system in coal mines. Issue 2 (23rd February 2020) - Ji, Jingwei; Li, Ningning; Chang, Zhangyu; Fan, Yujie; Ni, Lu
ABSTRACT: The paper designed a new type of mine cooling method. A small-scale experimental device was used to study the heat transfer characteristic parameters of the water film board of the core component of the method. Combined with the heat transfer model and experimental data, the average thermal conductivity and heat-absorbing efficiency were calculated to 0.0085 W/m·K and 85%. By setting different heat flux values, the roadway temperature dropped by 5.6°C to 22.1°C at a water flow rate of 25 ml/s. The paper also calculated the temperature rise value of a 100-m-long actual roadway after installing the cooling system through numerical simulation.